OPPORTUNITIES FOR THE STRATOSPHERIC COLLECTION OF DUST FROM SHORT-PERIOD COMETS - Messenger S. (My University, 2002)
We have identified four comets which have produced low-velocity Earth-crossing dust streams within the past century: 7P/Pons-Winnecke, 26P/Grigg-Skjellerup, 73P/Schwassmann-Wachmann 3, and 103P/Hartley 2. These comets have had the rare characteristics of low eccentricity, low inclination orbits with nodes very close to 1 AU. Dust from these comets is directly injected into Earth-crossing orbits by radiation pressure, unlike the great majority of interplanetary dust particles collected in the stratosphere which spend millennia in space prior to Earth-encounter. Complete dust streams from these comets form within a few decades, and appreciable amounts of dust are accreted by the Earth each year regardless of the positions of the parent comets. Dust from these comets could be collected in the stratosphere and identified by its short space exposure age, as indicated by low abundances of implanted solar-wind noble gases and/or lack of solar flare tracks. Dust from Grigg-Skjellerup probably has the highest concentration at Earth orbit. We estimate that the proportion of dust from this comet will reach at least several percent of the background interplanetary dust flux in the >40 μm size range during April 23–24 of 2003.